ENHANCED OBSERVABILITY OF CLOUD-NATIVE APPLICATIONS IN DATA ANALYTICS ARCHITECTURES - Abhilash Nagilla , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the evolution and implementation of observability frameworks in cloud-native applications, focusing on addressing the challenges of monitoring distributed systems through OpenTelemetry-compliant solutions. The article presents a comprehensive multi-layered observability architecture that integrates logging, metrics collection, and distributed tracing following CNCF best practices to provide enhanced visibility into cloud-native environments. By implementing standardized observability patterns and OpenTelemetry specifications, the framework demonstrates significant improvements in operational efficiency, system performance, and incident resolution capabilities through experimental validation in a production-grade microservices environment. The proposed framework successfully addresses the complexities of modern cloud-native architectures while providing actionable insights for optimizing system behavior and maintaining reliability. The implementation aligns with CNCF's observability principles and leverages OpenTelemetry's instrumentation capabilities to ensure standardized data collection, consistent context propagation, and seamless integration with existing cloud-native ecosystems.